Image Encryption Algorithm Based on a Novel Improper Fractional-Order Attractor and a Wavelet Function Map - Jian-feng Zhao; Shu-ying Wang; Li-tao Zhang; Xiao-yan Wang (Journal of Electrical and Computer Engineering)
This paper presents a three-dimensional autonomous chaotic system with high fraction dimension. It is noted that the nonlinear characteristic of the improper fractional-order chaos is interesting. Based on the continuous chaos and the discrete wavelet function map, an image encryption algorithm is put forward. The key space is formed by the initial state variables, parameters, and orders of the system. Every pixel value is included in secret key, so as to improve antiattack capability of the algorithm. The obtained simulation results and extensive security analyses demonstrate the high level of security of the algorithm and show its robustness against various types of attacks.